Characterization of Lasiodiplodia theobromae causing leaf blight disease of coconut - Ramjegathesh, R.; Johnson, I.; Hubali, K. Manjunath; Maheswarappa, H.P. (Journal of Plantation Crops, 2019)
Coconut leaf blight pathogen Lasiodiplodia theobromae (Pat.) was characterized based on morphological, cultural characters and Internal Transcribed Spacer (ITS) sequences. Pathogen isolates collected from various coconut growing areas of Tamil Nadu, India showed significant differences in the colony morphology, colour, spore dimensions and fruiting bodies. Molecular characterization by partial sequencing of ITS region confirmed the identity of pathogen as L. theobromae. Among the several methods of inoculation employed to establish the pathogenicity, pinprick method with spraying of conidial suspension (105 spores mL-1) and spot application of mycelial mat (5 mm disc) at the inoculation site produced typical necrotic spots and lesions on coconut leaves of West Coast Tall, Arasampatti Tall, Chowghat Orange Dwarf and Chowghat Green Dwarf. Koch’s postulates were established to confirm pathogenicity. The result of the study helps to streamline the existing management strategies.